Use of Potential Probiotic Lactic Acid Bacteria (LAB) Biofilms for the Control of Listeria monocytogenes, Salmonella Typhimurium, and Escherichia coli O157:H7 Biofilms Formation - Gómez, Natacha C.; Ramiro, Juan M. P.; Quecan, Beatriz X. V.; de Melo Franco, Bernadette D. G. (Frontiers in Microbiology, 2016)
Use of probiotic biofilms can be an alternative approach for reducing the formation of pathogenic biofilms in food industries. The aims of this study were: (i) to evaluate the probiotic properties of bacteriocinogenic (L. lactis VB69. L. lactis VB94, Lactobacillus sakei MBSa1 and Lb curvatus MBSa3) and non-bacteriocinogenic (L. lactis 368, Lb helveticus 354, Lb. casei 40 and Weissela viridescens 113) lactic acid bacteria (LAB) isolated from Brazilian´s foods and (ii) to develop protective biofilms with these strains and test them for exclusion of Listeria monocytogenes, Escherichia coli O157:H7 and Salmonella Typhimurium. LAB were tested for survival in acid and bile salt conditions, surface properties, biosurfactant production, β-galactosidase and gelatinase activity, antibiotic resistance and presence of virulence genes. Most strains survived exposure to pH 2 and 4% bile salts. The highest percentages of auto-aggregation were obtained after 24 h of incubation. 67% auto-aggregation value was observed in W. Viridescens 113 and Lb. curvatus MBSa3 exhibited the highest co-aggregation (69% with L. monocytogenes and 74.6% with E.coli O157:H7), while the lowest co-aggregation was exhibited by W. viridescens 113 (53.4% with L. monocytogenes and 38% with E. coli O157:H7). Tests for hemolytic activity, bacterial cell adherence with xylene and drop-collapse confirmed the biosurfactant-producing ability of most strains. Only one strain (L. lactis 368) produced β-galactosidase. All strains were negative for virulence genes cob, ccf, cylLL, cylLs, cyllM, cylB, cylA and efaAfs and gelatinase production. The antibiotic susceptibility tests indicated that the MIC for ciprofloxacin, clindamycin, gentamicin, kanamycin and streptomycin did not exceed the epidemiological cut-off (ECOFF) suggested by the European Food Safety Authority. Some strains were resistant to one or more antibiotics and resistance to antibiotics was species and strain dependent. In the protective biofilms assays, strains L. lactis 368 (bac-), Lb. curvatus MBSa3 (bac+) and Lb. sakei MBSa1(bac+) resulted in more than six log reductions in the pathogens counts when compared to the controls. This effect could not be attributed to bacteriocin production. These results suggest that these potential probiotic strains can be used as alternatives for control of biofilm formation by pathogenic bacteria in the food industry, without conferring a